Counting Your Chickens With Markov Chains. Issue 3 (27th May 2019) - McCune, David; McCune, Lori
Summary: We use Markov chains to analyze the cooperative children's game, Count Your Chickens! . Similar to Chutes and Ladders or Monopoly, this game involves movement of a token on a game board in which the movement is determined by pure chance. We use Markov chains to determine the win probability for the game and the win probability for variants of the game in which we change the structure of the underlying game board.